2018
DOI: 10.1049/mnl.2018.5132
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the flow of R1270‐based nanorefrigerants in a circular tube subject to uniform heat flux

Abstract: In this work, turbulent convective heat transfer of propylene (R1270)-based nanorefrigerant in a circular tube with a uniform heat flux of 20 kW/m 2 is numerically investigated using different types of nanoparticles namely Al 2 O 3 , CuO, SiO 2 and ZnO with a volume concentration ranging from 0 to 5%. Computations have been carried out using the commercial CFD code Fluent for Reynolds number ranging from 20,000 to 100,000 and a nanoparticle diameter of 30 nm. Results in terms of the average convective heat tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Figure 11 shows the comparison of pressure drop data for Al 2 O 3 -R718 nanorefrigerants at a particle volume fraction of 0.25% with pressure drop predictions made by using Eq. (25). The pressure drop data for Al 2 O 3 -R718 nanorefrigerant and the base fluid is summarised in Table 3.…”
Section: Pressure Drop Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 11 shows the comparison of pressure drop data for Al 2 O 3 -R718 nanorefrigerants at a particle volume fraction of 0.25% with pressure drop predictions made by using Eq. (25). The pressure drop data for Al 2 O 3 -R718 nanorefrigerant and the base fluid is summarised in Table 3.…”
Section: Pressure Drop Analysismentioning
confidence: 99%
“…Ahmed et al [22] conducted a numerical investigation for analysing the thermally radiative rotating flow of Maxwell nanofluid and concluded that the Brownian motion enhances the temperature field. Furthermore, few researchers have also conducted experimental and numerical studies on refrigerant based nanofluids (also known as nanorefrigerants) [23][24][25][26][27][28][29]. Helvaci and Khan [23] observed that the total entropy generation decreases with increase in Reynolds number in case of HFE 7000-based nanorefrigerants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation